Kegiatan Guru Seni Budaya (Musik) Di Kelas VII SMP N 3 Muaro Bungo Jambi Dalam Melaksanaan Kurikulum 2013 Pada Masa Pandemi Covid-19 - Amdika Tri Sakti Tri Sakti; Esy Maestro (FBS Universitas Negeri Padang, 2020)
The research problem is motivated by the existence of teachers’ activities in implementing 2013 Curriculum, especially in the form of implementing curricular activities (learning and non-learning) during Covid-19 pandemic. This is due to the fact that even though the teachers do not teach students face to face, curricular activities at school must be conducted both in the form of online learning and other non-learning activities. This study aims to explain various non-face-to-face curricular activities which can be conducted by music teachers at SMP Negeri 3 Muaro Bungo Jambi during the Covid-19 Pandemic.This is a qualitative research using descriptive analysis approach. The research object was music teachers at SMP Negeri 3 Muaro Bungo Jambi. The research instruments were observation, interview, and documentation study. The results explain that since the government has implemented health protocol rules to prevent Covid-19 transmission in schools, the music teachers at SMP Negeri 3 Muaro Bungo Jambi continue to carry out non-face-to-face curricular activities. The learning activities carried out online by teachers. In addition, the teachers conduct other non-learning curricular activities such as adjusting semester programs, reconstructing lesson plans, simplifying subject matters, making video tutorials for teaching preparation, and so on.